2016
DOI: 10.2352/issn.2470-1173.2016.4.ervr-417
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Native Support for Oculus and Leap Motion in a Commercial Engineering Visualization and Analysis Platform

Abstract: While previous research in academia points to the ability of Natural User Interfaces (NUIs) and low-cost display devices to help users better understand a design, there does not exist much research on how these devices can be integrated into existing legacy code used by engineering and design firms. The lack of commercial engineering software that integrates NUIs and low-cost display devices, like the Oculus Rift, can be attributed to the fast changing device market and the lack of awareness many engineering s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…MacAllister et al presented one of the first proof of concept systems integrating the Leap Motion and Oculus Rift DK2 into a commercial engineering visualization and analysis package called Siemens' Teamcenter R Lifecycle Visualization Mockup. During a study it was shown that these two devices together can provide real time, fluid interaction in a commercial engineering platform [50]. Different gestures were used for this purpose: direction-based rotation was triggered by a swipe gesture, the zoom in/out feature by a moving forward/backward gesture, and gesture tracking was turned on by closing the right fist and turned off by using the left one.…”
Section: Hand Interaction In Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…MacAllister et al presented one of the first proof of concept systems integrating the Leap Motion and Oculus Rift DK2 into a commercial engineering visualization and analysis package called Siemens' Teamcenter R Lifecycle Visualization Mockup. During a study it was shown that these two devices together can provide real time, fluid interaction in a commercial engineering platform [50]. Different gestures were used for this purpose: direction-based rotation was triggered by a swipe gesture, the zoom in/out feature by a moving forward/backward gesture, and gesture tracking was turned on by closing the right fist and turned off by using the left one.…”
Section: Hand Interaction In Vrmentioning
confidence: 99%
“…MacAlister et al mentioned in their work that "product design in today's globalized world requires quick turnarounds to maintain profitability" [50]. As mentioned earlier, Design Engineering is an interdisciplinary field, and therefore, the teams consist of diverse interdisciplinary backgrounds enabling concurrent design.…”
Section: Acceleration By Immersion?mentioning
confidence: 99%
See 1 more Smart Citation